The Role Of Financial Performance In The Disclosure Of Sustainability Reportd In State-Owned Enterprises - Nasihin, Ihsan; Fitriana, Avincennia Vindy; Arimurti, Trias; Purwandari, Dian (Program Pascasarjana STIE Amkop Makassar, 2023)
A sustainability report is a report published by a company, the contents of which are information about the company's social activities. Currently, there are still many companies that often do not pay attention to the social and environmental impacts of their business activities. For this reason, pressure and explanation are needed regarding the importance of companies disclosing sustainability reports whose aim is to help improve company performance. The research that will be used in this research is a quantitative method using a descriptive statistical approach. The data that will be used in this research is secondary data using population and samples in data collection. The data analysis technique that will be used in this research is to carry out multiple regression analysis. The results of the research that has been conducted show that financial performance has a positive effect on the disclosure of sustainability reports